2023
DOI: 10.1161/hypertensionaha.123.21224
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Intake and Blood Pressure Levels: A Dose-Response Meta-Analysis of Nonexperimental Cohort Studies

Abstract: BACKGROUND: Alcohol consumption may increase blood pressure but the details of the relationship are incomplete, particularly for the association at low levels of alcohol consumption, and no meta-analyses are available for nonexperimental cohort studies. METHODS: We performed a systematic search of longitudinal studies in healthy adults that reported on the association between alcohol intake and blood pressure. Our end points were the mean differences ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
(117 reference statements)
1
8
0
Order By: Relevance
“…A Mendelian study found genetic evidence of a causal relationship between alcohol consumption and cardiovascular diseases such as hypertension, coronary heart disease, and myocardial infarction, a relationship with a consistently increasing risk that rises exponentially with increasing intake (56). A Meta-analysis found a positive linear association between alcohol consumption and diastolic blood pressure (57). Our study found that moderate anthocyanin intake reduced the prevalence of hypertension in participants who were heavy and moderate drinkers.…”
Section: Discussionsupporting
confidence: 52%
“…A Mendelian study found genetic evidence of a causal relationship between alcohol consumption and cardiovascular diseases such as hypertension, coronary heart disease, and myocardial infarction, a relationship with a consistently increasing risk that rises exponentially with increasing intake (56). A Meta-analysis found a positive linear association between alcohol consumption and diastolic blood pressure (57). Our study found that moderate anthocyanin intake reduced the prevalence of hypertension in participants who were heavy and moderate drinkers.…”
Section: Discussionsupporting
confidence: 52%
“…Noteworthy is the significant reduction in blood pressure, specifically the registered decrease in SYS P in all patients. Systolic blood pressure is recognised as the most important preventable blood pressure-related risk indicator for cardiovascular disease [46][47][48][49], and MAP is recognised as an important marker directly related to the cardiovascular and cerebrovascular risk of stroke [43,44,48]. Finally, we perceived that pos-activity recovery was much faster on D30, as we could not find any significant differences in any variable except for LDF perfusion (Table 3 compares D0 and D30 in Phase 3).…”
Section: Discussionmentioning
confidence: 87%
“…ROS resulting in lipid peroxidation, protein oxidation, production of proinflammatory cytokines, and activation of mitogen-activated protein kinase (MAPK) and further leading to endothelial dysfunction [ 29 35 ]. Additionally, there is extensive evidence support that alcohol consumption is correlated with hypertension [ 4 , 36 – 38 ] which may accelerate the genesis of atherosclerosis. Numerous mechanisms, including increased sympathetic nervous system activity, increased intracellular Ca 2+ levels in vascular smooth muscle cells (VSMCs), increased renin-angiotensin system (RAS) activity, and endothelial dysfunction, had been implicated in the association between heavy alcohol consumption and hypertension [ 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%